Thriving Beyond Adversity: A Prospective Longitudinal Cohort Study Using a Strength-Based Approach Depicts Indigenous Adolescents with Less Adverse Childhood Experiences (ACEs) Had Fewer Neurodevelopmental Disorders (NDDs) - Md Irteja Islam; Bernadette Yan Yue Lam; Tuguy Esgin; Alexandra Martiniuk (Behavioral Sciences)
Improving social and emotional well-being (SEWB) among Indigenous adolescents is crucial. Since neurodevelopmental disorders (NDDs) are common in Indigenous people and adverse childhood experiences (ACEs) are important contributors to negative health outcomes throughout the lifespan, we investigated whether limited ACE exposure is associated with reduced risk of NDDs in Australian Indigenous teens using the data from multiple waves (Wave 1 to Wave 9, and Wave 11) of the Longitudinal Study of Indigenous Children (LSIC). We also examined the role of other protective factors, such as Indigenous cultural identity and school connectedness, against NDDs. A strengths-based approach using mixed-effects logistic regression models examined the protective effect of limited ACE exposure (from LSIC waves 1–9) on NDDs (outcome from LSIC wave 11), adjusting for sociodemographic factors. The NDDs included autism, ADHD, intellectual, neurological, and specific learning disabilities. Of the 370 individuals analysed, 73.2% valued Indigenous cultural identity, and 70.5% were strongly connected at school. More than one-fourth (27.8%) reported limited ACE exposure, while the majority was not diagnosed with NDDs (93%). Longitudinal analysis revealed limited ACE exposure was 6.01 times (95% CI: 1.26–28.61; p = 0.024) more likely to be protective against NDDs compared to those exposed to multiple ACEs. Moreover, valuing cultural identity (aOR = 2.81; 95% CI: 1.06–7.39; p = 0.038) and girls (aOR = 13.88; 95% CI: 3.06–62.84; p = 0.001) were protective against NDDs compared to their respective counterparts. Our findings highlight the need to prevent ACE exposure and promote Indigenous cultural identity in preventing negative health outcomes and the exacerbation of health inequities to strengthen the SEWB of Indigenous communities.